Social media influencers and their marketing effects on followers?: An exploratory study in restaurant review microblogs - Ying Zhou (2019)
The current study investigates the factors that influence the effects of social media influencers’ brand-related e-WOM on users. Moreover, the study evaluates the moderating impact of individualism/collectivism on consumers’ responses towards social media influencers’ e-WOM. The context of the study is focused on the Weibo microblogs related to restaurant reviews. By conducting an experimental survey, the study collected 463 valid data. The findings of the study indicate that the microblogs, either providing more product disclosure in contents and with higher degree of popularity, tend to enhance consumers’ greater cognitive trust on the bloggers. Whereas, the microblogs revealing more bloggers’ social disclosure in contents incline to induce consumers’ greater affective trust on the bloggers. The study also confirms that the effects of product disclosure and popularity on cognitive trust and the effect of social disclosure on affective trust are stronger when consumers are collectivism-oriented than when consumers are individualism-oriented. Moreover, higher cognitive trust can result in higher affective trust which, in turn, leads to consumers’ feedback intentions towards bloggers. Cognitive trust, affective trust, perceived enjoyment of reading e-WOM massages, and perceived usefulness of bloggers’ recommendations are all proved to have positive influences on consumers’ product attitudes. Additionally, the impact of cognitive trust on product attitudes is mediated by perceived usefulness. The findings of this study provide useful suggestions for bloggers and brands to implement effective e-WOM.